Continuous transition from gamma to beta dynamics during stress relaxation. (February 2023) - Gao, Y.R.; Tong, Y.; Song, L.J.; Shui, X.X.; Gao, M.; Huo, J.T.; Wang, J.-Q.
Abstract: Detecting and modulating the hierarchical relaxation kinetics of metallic glasses is important in understanding the nature of glass and critical in achieving superior properties. In this letter, the relaxation dynamics of Fe76 Si9 B10 P5 metallic glass are studied by stress relaxation and strain recovery experiments. The instant heterogeneous factor and the activation energy are calculated according to the Kohlrausch-Williams-Watts equation, which suggests a continuous transition from γ to β dynamics during stress relaxation. In fast process of dynamics, the strain can completely recover, while in the slow β relaxation process, the plastic strain emerges resulting from the contribution of an irreversible localized rearrangement. Our results suggest that the relaxation kinetics can be precisely controlled during the stress relaxation process. Graphical abstract: Image, graphical abstract